Thornthwaite Moisture Index for the Triângulo Mineiro, Brazilian Cerrado Region, Under Climate Change - Fischer Filho, João Alberto; Rosa, Giovani Bonício; Vieira, Julia Cristina Amâncio; Fuzzo, Daniela Fernanda da Silva (Sociedade & Natureza, 2025)
Climate change represents one of the main challenges of the 21st century for planning and sustainable development. However, little is known about how climate change can affect a region's climate zones. The objective was to evaluate probable changes in climatic zones using the Thornthwaite climate classification (1948). Historical series between 1981 and 2021 of rainfall and air temperature were used. The water balance was calculated from Thornthwaite and Mather. Thornthwaite's humidity index (1948) was used to classify localities according to their level of humidity and the scenarios RCP 2.6, RCP 4.5, RCP 6.0 and RCP 8.5 to analyze projections for the 21st century (period 2081–2100). The current characterization, with historical data, of the region's climate presented air temperature, rainfall and average potential evapotranspiration, respectively, of 22.4ºC, 1,318.8 mm and 1,123.74 mm, in addition to a water surplus of 391.04 mm and water deficit of 195.04 mm. The region currently has five climate indices, with a prevalence of more humid classes (B1, B2 and B3), corresponding to 62% of the territory. The results derived from the projections indicate reductions in climate classes and an increase in the area occupied by drier climates. For example, the percentage of area occupied by class C1 (dry subhumid) would increase from the current 8.4% to 69.68% in the RCP 8.5 scenario. The study of these change projections is important since profound consequences for the hydrology, ecology and social area of the region will take place, potentially harming agriculture, the region's main economic activity.